A review of primary and secondary influences on sport expertise - Baker, J.; Horton, S. (High Ability Studies, 2004)
Sport scientists have examined numerous factors influencing the acquisition and manifestation of high levels of performance. These factors can be divided into variables having a primary influence on expertise and variables that have a secondary influence through their interaction with other variables. Primary influences on expertise include genetic, training, and psychological factors while secondary influences include socio-cultural and contextual elements. This paper reviews the factors affecting the development of expert performance in sport and suggests directions for future research.